Taxonomic notes on Paratobias F. O. Pickard-Cambridge, 1900: updated diagnosis and a new species description (Araneae, Thomisidae, Stephanopinae) - Machado, Miguel; Guzati, Catherine; Teixeira, Renato Augusto (Zootaxa, 2025)
The recently revalidated genus Paratobias has its diagnosis and description updated in the present paper. The male of P. championi is described for the first time, and the new species P. invictus sp. nov. is described based on both sexes. New distribution records for the genus are provided.